Prognostic factors for heart valve surgery outcomes in Dr Sardjito General Hospital Yogyakarta, Indonesia - Wahyu Priyatno; . Supomo (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2019)
Heart valve disease is a serious health probem due its significant effect on mortality.Surgical intervention plays an importan roleinthe management of moderate to the severe valvular heart disease. The evaluation of the patientoutcomes has been widely accepted as one of the important steps to improve the quality of patient care.Recognition of post operative complications might significantly affect the patient quality of life.Therefore, the identification of prognostic factors and morbidity of heart surgery patients can provide valuable insights on improving the quality of patient care.This study aimedto investigat the prognostic factors for heart valve surgery outcomes in Dr. Sardjito General Hospital, Yogyakarta, Indonesia. This study was conducted using data ofpatient’s medical records who underwent heart valve surgeryincluded morbidities and their prognostic factors.The data were analyzed using Chi-square test and logistic regression with significance level of 0.05. During 2010 to 2014, 82 patients underwent heart valve surgeries at the hospital. The kidney disorders and heart failure were significantly associated with the patient morbidity (p<0.05),while the gender, pulmonary disease, angina, and impaired ventricular function were not (p>0.05). Multivariate analysis showed that the heart failure is the most significant factor of morbidity. The risk of New York Heart Association (NYHA) class 3 patients were 7.18 times compared with NYHA class 2 patients. In conclusion, the heart failure is the most significant factor for the morbidityof heart valve surgery followed by the kidney disorders at the Dr. Sardjito General Hospital.